LESYA UKRAINKA AND LUDMILA STARYTSCHA-CHERNACHIVSKA: FEATURES OF CULTURAL PRESENCE - Romanov, S. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
In this article the two different models of entry into the culture over life and creative works of Lesya Ukrainka and L. Starytscha-Chernachivska are outlined. The Lesya Ukrainka’s path is path of constant search for new opportunities for self-realization in unity with the renunciation of parental paths in public life and work. The L. Starytscha-Chernachivska’s path (despite initial search own social position and literary style) is path all the same merges with the “parent” mainstream. In the works it meant the rejection of modernism and return to realism / romanticism.